Rereading the Qur'an Text as Women's Liberation Perspective Asma Barlas - Zaeni Anwar; Nailul Khoiril Marom; Nur Arfiyah Febriani (Seutia Hukamaa Cendekia, 2025)
This study examines Asma Barlas's thoughts on the rereading of the Qur'an text as a form of liberation of women from patriarchal interpretation. Using a descriptive qualitative approach and a literature review, this study examines Asma Barlas' main works, especially Believing Women in Islam: Unreading Patriarchal Interpretations of the Qur'an, as well as secondary literature relevant to gender interpretation and Islamic feminism. The study's results show that Asma Barlas rejects the notion that the Qur'an is patriarchal. He emphasized that gender bias in interpretation is a historical and social product of male mufasir who live in a patriarchal system. Using historical and hermeneutic arguments, Barlas constructs an epistemology of egalitarianism rooted in the concept of monotheism, in which there is no hierarchy of power between men and women. His reinterpretation of verses such as Q.S. An-Nisa [4]:34 and Q.S. Al-Baqarah [2]:228 affirms that the terms qiwamah and